Vitamin D – a key player in diabetes management – a review - Pant, Niranjan; Huang, Mingwei (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Diabetes mellitus is a major health concern around the world and requires new management strategies. Several investigations have shown the connection between a lack of vitamin D and diabetes and its complexities. The objective of this review was to investigate the impact of vitamin D on maintaining glucose levels. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The material and methods section of this review involved conducting a literature review. This process included searching databases such as PubMed Crossref, Google Scholar, Scopus, Web of Science, Embase, and the Cochrane Library for studies examining the relationship between vitamin D levels and complications of diabetes. These databases were selected to ensure a comprehensive exploration of the existing literature to provide a comprehensive analysis of the relationship between vitamin D status and diabetic complications. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. Vitamin D plays an important role in preventing macrovascular and microvascular complications such as diabetic retinopathy, diabetic neuropathy, diabetic kidney disease, and diabetic foot ulcer in people with diabetes mellitus. Correcting vitamin D deficiency through optimal dosages of vitamin D supplements is an effective way to address the management and prevention of macrovascular and microvascular complications in diabetic individuals. This review emphasizes the critical importance of vitamin D supplementation for individuals with diabetes mellitus as it significantly maintains optimal blood glucose levels and reduces diabetes-associated risks. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Vitamin D is vital for managing and preventing diabetes complications. It stabilizes blood glucose levels and reduces risks of complications like retinopathy, neuropathy, kidney disease, and foot ulcers. Including it in diabetes management is crucial for better health outcomes.